O emprego rural no estado de Goiás na década de 90 - Magalhães, Marcos Ferreira de (2002)
The present job has in view to describe and to discuss about the rural factor’s question and about the little production’s participation in a local and regional context like an economic option in agrícultural frontier. For this, will be discussed the agricullural occupations charactcr and non-agricultural in Goiano peoplc, observing tlicir file about the employmenfs composition and of the income thal carne from of these occupations, like its degree of participation, by part of economic activity, in generalion ofthe State economic development, of the place and ofthe country. Thus, witli the intention of discussions, according to PNAD’s data about agricultural activities and non-agricultural activities in Goiano people, was described like these points are assuming a special place in rural areas so contradictories from view point ofthe agricultural scenery.